Cesiumlead based inorganic perovskite quantum-dots as interfacial layer for highly stable perovskite solar cells with exceeding 21% efficiency. (June 2019) - Akin, Seckin; Altintas, Yemliha; Mutlugun, Evren; Sonmezoglu, Savas
Abstract: Despite the excellent photovoltaic performances of perovskite solar cells (PSCs), the instability of PSCs under severe environment (e.g. humidity, light-induced, etc.) limits further commercialization of such devices. Therefore, in recent years, research on the long-term stability improvement of PSCs has been actively carried out in perovskite field. To address these issues, we demonstrated the incorporation of ultra-thin interfacial layer of inorganic CsPbBr1.85 I1.15 perovskite quantum-dots (PQDs) that can effectively passivate defects at or near to the perovskite/hole transport material (HTM) interface, significantly suppressing interfacial recombination. This passivation layer increased the open circuit voltage (Voc ) of triple-cation perovskite cells by as much as 50 mV, with champion cells achieving Voc ∼ 1.14 V. As a result, we obtained hysteresis-free cells with the efficiency beyond 21%. More importantly, devices based on such architecture are capable of resisting humidity and light-induced. Remarkably, the device employing CsPbBr1.85 I1.15 demonstrated a superb shelf-stability aganist to humidity under ambient conditions (R.H.≥40%), retaining nearly 91% of initial efficiency after 30 days, while the efficiency of control device rapidly dropped to 45% from its initial value under the same conditions. Besides benefiting from the high moisture resistivity as well as supressed ion migration, PSCs based on PQDs showed better operational stability (retaining 94% of their initial performance) than that of the PQDs-free one under continuous light irradiation over 400 h. In addition, a faster PL decay time of 4.66 ns was attained for perovskite/PQDs structure (5.77 ns for only PQDs structure) due to the favorable energy transfer at the interface, indicating a Förster resonance energy transfer (FRET) mechanism. This work indicates that inorganic PQDs are important materials as interlayer in PSCs to supremely enhance the device stability and efficiency. Graphical abstract: Image 1 Highlights: We demonstrated the incorporation of ultrathin interfacial layer of inorganic CsPbBrx I3-x perovskite quantum-dots (PQDs). Device employing CsPbBrx I3-x demonstrated a superb shelf-stability aganist to humidity under ambient conditions (R.H.≥40%). PSCs based on PQDs showed better operational stability under continuous light irradiation over 400 h.